Path changes in the movement of English Premier League soccer players - Robinson, G.; O`donoghue, P.; Wooster, B. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Traditional time-motion analysis methods have analysed broad locomotive movements and distances covered by players in different speed ranges. It is necessary to consider path changes made during movements in order to understand the agility requirements of soccer. The purpose of the current investigation was to describe the path changes performed in English FA Premier League soccer. METHODS:The Prozone® path change identification system identified three different types of path change within accurate timed player co-ordinate data gathered by the Prozone3® player tracking system. Data for 90 minute plus performances of 180 different players were included in the current investigation. RESULTS:The players performed 38±15 path changes of 45o to 135o to the left, 35.5±14.3 path changes of 45o to 135o to the right and 20.2±90 path changes of 135o or greater. Positional role had a significant influence on the number of each type of path change performed with midfielders performing more of each path change type than defenders and forwards. There was also a significant difference in the number of each type of path change performed between different 15 minute periods of the match with more of each type being performed in the first 15 minutes and fewer of each type being performed between 60 minutes and 75 minutes than during any other period. CONCLUSION:These results have implications for agility requirements of soccer match play that conditioning coaches should be aware of.